The Dual Effect Of Conflict And Work Environment On Employee Efficiency: Insights From PT. United Tractors Tbk-Banjarmasin - Juwita Cahaya, Ramadha; Aida, Vitria; Ana Sofia, Herawati (CV ODIS, 2025)
This study aimed to examine the impact of workplace conflict and the work environment on employee performance at PT. United Tractors Tbk in Banjarmasin. A quantitative research design was employed, with a sample of 43 employees selected using proportional random sampling from a total population of 122 employees. Primary data were collected through questionnaires, while secondary data were obtained through observations and literature review. The collected data were analyzed using descriptive analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing, including the coefficient of determination (R²), F-test, and t-test, with the assistance of SPSS 26 software. The findings indicate that (1) workplace conflict has a positive and significant effect on employee performance, with a coefficient value of 2.194 and a significance level of 0.034; (2) the work environment also has a positive and significant effect on employee performance, with a coefficient value of 2.193 and a significance level of 0.034; and (3) the combination of workplace conflict and the work environment has a significant joint effect on employee performance, as evidenced by an F-value of 35.272 and a probability of 0.000. These results suggest that effective conflict management and a conducive work environment are crucial factors in enhancing employee productivity.